2021
DOI: 10.3390/medicina57101077
|View full text |Cite
|
Sign up to set email alerts
|

Does the EU COVID Digital Certificate Strike a Reasonable Balance between Mobility Needs and Public Health?

Abstract: The need to fight a highly aggressive virus such as SARS-CoV-2 has compelled governments to put in place measures, which, in the name of health protection, have constrained many freedoms we all enjoy, including freedom of movement, both nationally and within the European Union. In order to encourage and facilitate the return to free movement, the European Parliament has launched a “COVID-19 digital certificate.” A spirited debate centered around the use of this certificate is still ongoing among scholars, many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…In addition, our findings showed that as opposed to the other domestic settings, in the case of visiting a GP for a non-urgent matter, respondents were more willing to use immunity certificates that prioritised convenience . The reason for choosing this option could be justified by the fact that respondents valued the public health benefits of using certificates in this context as more important compared with the option than prioritised privacy 44. Also, this means that respondents in this survey preferred access to primary care services to be seamless without a need for patients to show proof of their immunity status in a digital or physical format.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, our findings showed that as opposed to the other domestic settings, in the case of visiting a GP for a non-urgent matter, respondents were more willing to use immunity certificates that prioritised convenience . The reason for choosing this option could be justified by the fact that respondents valued the public health benefits of using certificates in this context as more important compared with the option than prioritised privacy 44. Also, this means that respondents in this survey preferred access to primary care services to be seamless without a need for patients to show proof of their immunity status in a digital or physical format.…”
Section: Discussionmentioning
confidence: 99%
“…For the use and uptake of such certificates to be successful the public and businesses should be educated, and nationwide public health campaigns should promote this shared understanding explaining the extent to which personal data, if any, is shared on verification of someone’s immunity status. Researchers examining the implementation of the European Union (EU)’s COVID-19 digital certificate for international travel (known as green pass) highlighted the importance of campaigns to educate the public about the purpose, opportunities and limitations of these certificates too 44. In addition to educating the public and promoting the importance of certification for public health, the presence of such nationwide campaigns is important for transparency reasons too.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, regardless of the uniform regulatory and technical framework, EU Member States are still eligible to enforce legal actions autonomously to a certain degree, so national authorities may still apply different travelling and border entry conditions [ 5 , 6 ]. Obligations of healthcare providers with regard to electronic records of vaccinations and test results are subject to national regulations [ 7 , 8 ] and therefore may differ between the Member States. The DCC holds vital information: name, surname, date of birth, date of issue, information on the negative test results, vaccination against the COVID-19, recovery from the COVID-19, and a distinctive certificate identifier.…”
Section: Introductionmentioning
confidence: 99%